Projeto de economia solidária no BNB: subsídios para avaliar a aplicação do Fundo de Desenvolvimento Regional (FDR ) - Lima, Margarida Maria Feliciano de (2008)
This work is an examination of a mutual economy’s project named “Coité-Pedreiras Dressmakers’ joint responsibility support group”. This project took, in 2004, financial support of the Regional Development Found (FDR). This work draws a methodology on its own that explores the investigated experience’s qualitative features and shows a compact discussion about the development and underdevelopment, doing a survey of the instruments that are used for northeastern development, including the Banco do Nordeste do Brasil S/A (BNB) with its particular acts of productive sector’s maintainer and its preparation and dissemination of scientific knowledge executed by Technical Office of Economical Studies of Northeastern, which is FDR’s manager. As a reference of a theory’s concept for basing the experience is made a description of mutual economy from utopian socialism and from the cooperative help, doing a discussion about the mutual economy question as either the emancipated proposition against the industrial capitalism or an alternative for job’s crisis. Finally, the work brings the Coité-Pedreiras experience dressmakers and emphasizes their social conquests: autonomy, equal access to learning and income; their politics conquest: key protagonists, equal participation to conduct projects, in decisions, in the work organization and in the leadership formation, etc. and their economy conquests: markets, goods and basic services access